社交媒体对马来西亚青年首投族的影响：从信息获取到投票意愿的探索性分析 - Wang, Yuan; 王, 源 (2024)
In December 2021, Malaysia lowered the voting age from 21 to 18. The newly eligible young voters, born in the digital era, have been identified as the most active and frequent users of social media. They are also touted as a crucial demographic in elections, prompting political parties and candidates to actively seek their support. On this ground, the study applied Media System Dependency Theory (MSDT) as its analytical framework and used the 2022 15th General Election (GE15) and the 2023 state elections as case studies. The study explored which social media platforms and types of political information are preferred by these young voters, who predominantly rely on social media for political insights, as well as examined how social media influences their voting intentions. Via online survey questionnaire, the study surveyed 224 Malaysian young first-time voters aged between 18 and 24 from various ethnic backgrounds from April 21 to May 20, 2024. The results reveal that Facebook is the most favoured social media platform for accessing political information among these young voters. They are particularly interested in political content presented in the form of short videos, and favoured posts, tweets, and videos disseminated from social media pages managed by news media. Furthermore, these young first-time voters demonstrated strong participation in voting and exhibit a high level of voting intention in elections. The study also highlights the role of social media in helping young voters obtain and understand both domestic and international political issues, as well as in shaping their decisions on which party or candidate to support.